2013
DOI: 10.1016/j.bbr.2013.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Links between breeding readiness, opioid immunolabeling, and the affective state induced by hearing male courtship song in female European starlings (Sturnus vulgaris)

Abstract: Male courtship vocalizations represent a potent signal designed to attract females; however, not all females find male signals equally attractive. We explored the possibility that the affective state induced by hearing courtship vocalizations depends on the motivational state of a receiver. We used a conditioned place preference test of reward to determine the extent to which the rewarding properties of hearing male courtship song differed in female European starlings categorized as nest box owners (a sign of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 78 publications
5
21
0
Order By: Relevance
“…the nest cavity exploration principal components factor). These findings are consistent with a previous study in starlings demonstrating greater immunolabeling measurements for the protein product of PENK, met-enkephalin, in the mPOA of female starlings that explored nest boxes compared with those that did not (Riters et al, 2013). We also found that PENK mRNA correlated positively with ERα mRNA expression in the mPOA.…”
Section: Circulating Estradiol Related To Nest Cavity Exploration Butsupporting
confidence: 92%
See 4 more Smart Citations
“…the nest cavity exploration principal components factor). These findings are consistent with a previous study in starlings demonstrating greater immunolabeling measurements for the protein product of PENK, met-enkephalin, in the mPOA of female starlings that explored nest boxes compared with those that did not (Riters et al, 2013). We also found that PENK mRNA correlated positively with ERα mRNA expression in the mPOA.…”
Section: Circulating Estradiol Related To Nest Cavity Exploration Butsupporting
confidence: 92%
“…In female starlings, measurements of immunolabeling for met-enkephalin were higher in mPOA and VMH in females that explored compared with those that did not explore nest cavities (Riters et al, 2013). Met-enkephalin labeling measurements in VMH also correlated positively with the number of times females entered nest cavities and with reward induced by hearing male song (measured using conditioned place preference; Riters et al, 2013). Opioids in both the mPOA and VMH underlie reward induced by paced mating behavior in female rats (García-Horsman et al, 2008).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations